Pemberdayaan Industri Olahan Tembakau: Studi Implementasi Kebijakan di Kabupaten Sidoarjo - Ryan Gymnastiar Alwin; Agus Sukristyanto; Muhammad Roisul Basyar (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The tobacco processing industry plays a strategic role in the economy through its contribution to excise revenues, yet it also faces serious challenges such as the proliferation of illegal cigarettes and limited capacity among small-scale entrepreneurs. This study aims to analyze the implementation of tobacco industry empowerment policies in Sidoarjo Regency using Michael Hill’s implementation theory, which includes five variables: policy characteristics, policy transfer process, inter-organizational relationships, external environment, and target group response. This research uses a qualitative method with a case study approach. The findings show that policies such as SIINas, SIHT, and WASDAL have been implemented but remain suboptimal due to technical, coordinative, and social constraints. Business actors appreciate the empowerment programs but still face technical difficulties, market distortion due to illegal products, and a lack of continuous assistance. Therefore, increased institutional synergy, enhanced digital systems, and consistent law enforcement against illegal cigarettes are recommended to create a healthy and competitive industrial climate..